Role of Lactobacillus helveticus on Flavor Formation in Cheese: Amino Acid Metabolism - Widyastuti, Yantyati; Lisdiyanti, Puspita; Tisnadjaja, Djadjat (Annales Bogorienses, 2014)
Lactic acid bacteria, mainly lactobacilli, play an important role in cheese making. Their role can be divided into starters and non-starters or secondary microorganisms. Lactobacillus helveticus, an obligately homofermenter and thermophilic bacterium, has unique properties as a starter because of its ability to induce strong impact on cheese flavor. The bacteria are known to be prototrophic for 5 amino acids and auxotrophic for 13 amino acids. It is interesting that the conversion of aromatic amino acids, branch chain amino acids, and methionine into volatile and nonvolatile compounds by L. helveticus is thought to represent the rate-limiting step in the formation of mature flavor and aroma in cheese. The addition of a highly autolytic L. helveticus to a starter system could significantly increase the formation of flavor precursor and some volatile compounds during cheese ripening. This article focuses on the contribution of L. helveticus to flavour compound formation in cheese with particular emphasis on amino acid metabolism.